THE EFFECTIVENESS OF CLASSROOM MANAGEMENT STRATEGIES ON STUDENTS' ACADEMIC ACHIEVEMENT IN PHNOM PENH, CAMBODIA - Seam Chanthoul (Jurnal As-Salam, 2026)
Effective classroom management is widely recognized as a key factor in improving students' academic achievement; however, empirical evidence from the Cambodian secondary education context remains limited. This study aimed to examine the relationship between classroom management strategies, particularly instructional supervision, and student academic achievement in a private secondary school in Phnom Penh, Cambodia. A quantitative descriptive survey design was employed involving 45 secondary school teachers. Data were collected using an online questionnaire and analyzed using Pearson correlation with SPSS at the 0.01 significance level. The findings revealed a significant positive relationship between classroom management strategies and student academic achievement (r = 0.538, p < 0.01). Instructional supervision was also positively associated with student engagement (r = 0.527, p < 0.01) and student self-efficacy (r = 0.413, p < 0.01), indicating that effective classroom management contributes to creating supportive learning environments that foster active participation, confidence, and improved academic performance. These findings highlight the importance of strengthening teachers' classroom management competencies through continuous professional development and integrating classroom management and instructional leadership into teacher education programs.